In situ detection of plasma exosomal microRNA for lung cancer diagnosis using duplex-specific nuclease and MoS2 nanosheets. Issue 6 (25th January 2021) - Gao, Zibo; Yuan, Huijie; Mao, Yanhua; Ding, Lihua; Effah, Clement Yaw; He, Sitian; He, Leiliang; Liu, Li-e; Yu, Songcheng; Wang, Yilin; Wang, Jia; Tian, Yongmei; et al.
Abstract : An in situ detection of plasma exosomal microRNA for lung cancer diagnosis using duplex-specific nuclease and molybdenum disulfide nanosheets. Abstract : MicroRNAs (miRNAs) encapsulated in tumor-derived exosomes are becoming ideal biomarkers for the early diagnosis and prognosis of lung cancer. However, the accuracy and sensitivity are often hampered by the extraction process of exosomal miRNA using traditional methods. Herein, this study developed a fluorogenic quantitative detection method for exosomal miRNA using the fluorescence quenching properties of molybdenum disulfide (MoS2 ) nanosheets and the enzyme-assisted signal amplification properties of duplex-specific nuclease (DSN). First, a fluorescently-labeled nucleic acid probe was used to hybridize the target miRNA to form a DNA/RNA hybrid structure. Under the action of the DSN, the DNA single strand in the DNA/RNA hybrid strand was selectively digested into smaller oligonucleotide fragments. At the same time, the released miRNA target triggers the next reaction cycle, so as to achieve signal amplification. Then, MoS2 was used to selectively quench the fluorescence of the undigested probe leaving the fluorescent signal of the fluorescently-labeled probe fragments. The fluorometric signals for miRNA-21 had a maximum excitation/emission wavelength of 488/518 nm. Most importantly, the biosensor was then applied for the accurate quantitative detection of miRNA-21 in exosome lysates extracted from human plasma and this method was able to successfully distinguish lung cancer patients from healthy people. This biosensor provides a simple, rapid, and a highly specific quantitative method for exosomal miRNA and has promising potential to be used in the early diagnosis of lung cancer.